Food cravings, appetite, and snack-food consumption in response to a psychomotor stimulant drug: the moderating effect of “food-addiction” - Davis, Caroline; Levitan, Robert D.; Kaplan, Allan S.; Kennedy, James L.; Carter, Jacqueline C. (Frontiers in Psychology, 2014)
There is mounting evidence that many highly processed foods have addictive properties, and that some cases of compulsive overeating are behavioral addictions. While support for the Yale Food Addiction Scale (YFAS) as a valid diagnostic tool has been impressive and continues to increase, to date, no research has examined the food-addiction construct in response to an actual food stimulus, and in relation to direct measures of appetite and food consumption. As part of a larger community-based study of overeating in healthy adults who were predominately overweight and obese (aged 25-50 years), 136 participants completed the YFAS, of whom 23 met the diagnostic criteria for food addiction. They took part in a 2-day, double-blind, cross-over, single-dose drug challenge using a psychomotor stimulant (methylphenidate) and placebo. Participants were first assessed on ratings of appetite and food cravings after holding and tasting their favorite snack food, after which they were able to eat all or part of the snack, as they wished. Three separate repeated-measures Analysis of Variance (ANOVA) procedures were carried out, each with 2 between-subjects factors (Diagnosis: food addiction vs non-food addiction) and (Sex: male vs female) and 1 within-subjects factor (Days: drug vs placebo). As anticipated, for all three dependent variables, there was a significant main effect for Days with a response decrease from placebo to the drug condition. With respect to food cravings and appetite ratings, results indicated that the food-addiction group had significantly higher scores on both variables (p<0.0001). For food consumption, there was a significant Days x Diagnosis interaction (p=0.018) whereby the food-addiction group showed no food-intake suppression across days compared to the non-food-addiction group who demonstrated a significant decrease in snack-food consumption with methylphenidate. The finding that the food-addiction group was resistant to the food-intake suppression typic